Concentration of polycyclic aromatic hydrocarbons in zooplanktons of Bushehr coastal waters (north of the Persian Gulf). (March 2019) - Khaksar, Fatemeh; Manavi, Parisa Nejatkhah; Ardalan, Aria Ashja; Abedi, Ehsan; Saleh, Abolfazl
Abstract: In this study, polycyclic aromatic hydrocarbon contents in zooplanktons of coastal waters of Bushehr Province at the north of the Persian Gulf were evaluated. Zooplankton samples were collected from 18 stations in both summer and winter (2017), and their polycyclic aromatic hydrocarbon contents were measured by gas chromatography–mass spectrometry after ultrasound-assisted extraction. Results revealed that among 16 compounds that were analyzed, only 7 compounds were recognizable at both seasons. Pyrene was the most common individual compound of polycyclic aromatic hydrocarbons, whereas acenaphthene was the least individual compound found at both seasons. Additionally, the highest content of the measured compounds in both summer and winter was 16.4–75.9 ng/g and 17.3–93.7 ng/g, respectively. On the basis of the obtained results, the total concentration of polycyclic aromatic hydrocarbons was significantly higher in winter than in summer (P < 0.05). Highlights: PAHs were determined in zooplankton of Bushehr coastal waters. 7 compounds were recognizable at both seasons. Pyrene was the most common individual compound of polycyclic aromatic.